The influence of gender and academic training int he entrepreneurial intention of physical activity and sport sciences students - María Huertas González Serrano; Irena Valantine; Carlos Pérez Campos; Sergio Aguado Berenguer; Ferran Calabuig Moreno; Josep Joan Crespo Hervás (Intangible Capital, 2016)
Purpose: The objective of this article is to know if there are differences in the variables that explain the entrepreneurial intention of the Physical Activity and Sport Science students addressing academic training and gender of them.